Legal and administrative nature of concessions in Energy Law - Jabłoński, Maciej (Studia Ecologiae et Bioethicae, 2012)
Concessions are one of the elements of regulation of economic activity. Energy Law stipulates the conditions for obtaining a license for the production of energy. Due to the importance of the energy sector to the security of the State, matters relating to licensing procedures are regulated by Law and Regulations.